1981
DOI: 10.1126/science.6168020
|View full text |Cite
|
Sign up to set email alerts
|

Release of Immunoreactive Serotonin into the Lumen of the Feline Gut in Response to Vagal Nerve Stimulation

Abstract: Immunoreactive serotonin was detected in the lumen of the proximal jejunum of food-deprived cats. During perfusion of this intestinal segment in vivo, there was a constant basal rate of intraluminal secretion of this amine. The rate of secretion was significantly increased during efferent electrical stimulation of the cut cervical vagal nerves. This stimulatory effect was not altered after bilateral adrenalectomy was performed in the same animals. A synchronous release of substance P into the gut lumen was als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(31 citation statements)
references
References 10 publications
(5 reference statements)
3
28
0
Order By: Relevance
“…However, it remains unclear which 5-HT released from the enteric nervous system or EC cells plays a major role in mediating colonic motility. 5-HT is released from EC cells into the portal circulation or basolateral border of the mucosa (14), while others showed that 5-HT is released into the lumen of GI tract (1,12). Immunoelectron microscopic study revealed that aggregation of secretory granules of 5-HT was located in the apical and basolateral cytoplasm of EC cells in the rat duodenum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it remains unclear which 5-HT released from the enteric nervous system or EC cells plays a major role in mediating colonic motility. 5-HT is released from EC cells into the portal circulation or basolateral border of the mucosa (14), while others showed that 5-HT is released into the lumen of GI tract (1,12). Immunoelectron microscopic study revealed that aggregation of secretory granules of 5-HT was located in the apical and basolateral cytoplasm of EC cells in the rat duodenum.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, others showed that 5-HT is also released into the intestinal lumen in response to vagal nerve stimulation (1,20), luminal acidification (25), and food intake (10). Immunoelectron microscopic study showed the anatomical evidence that 5-HT is released from EC cells in response to an increase of luminal pressure of the rat duodenum (12).…”
mentioning
confidence: 99%
“…In these studies the mean perfusate concentration of 5-HT washed out to 60±60 ng/ml at the end of period I, peaked at 176.2±14.3 ,g/ml during period II, and returned to 3.8±1.7 ,ug/ml at the end of period (3,4,16,17). We have previously demonstrated, in a similar feline system, that electrical vagal nerve stimulation causes up to 20-fold elevations in the quantity of 5-HT and SP measured in saline-infused segments of proximal jejunum (1)(2)(3). In this study the effects of exogenously introduced 5-HT and SP on local blood flow were studied in the proximal feline jejunum.…”
Section: Resultsmentioning
confidence: 99%
“…It would be appear that serotonin is released from the enterochromaffin cells into both the circulation and the intestinal lumen (Ahlman et al, 1981;Gronstad et al, 1984) and the mechanisms for these releases have been shown to be independent in both cases (Money et aL, 1988). Furthermore, the release of serotonin seems to be regulated by either cholinergic, adrenergic and/or peptidergic nerves as well as by intraluminal stimuli (Ferrara et al, 1987;Gronstad et al, 1987).…”
Section: Serotonin (5-hydroxytryptamine) (5 Ht)mentioning
confidence: 99%